2024
DOI: 10.1186/s40001-024-01710-0
|View full text |Cite
|
Sign up to set email alerts
|

A rare inflammatory myofibroblastic tumor appearing both inside and outside the heart

Jiarong Li,
Jijia Liu,
Xingwang Yao
et al.

Abstract: Background Inflammatory myofibroblastic tumor (IMT) is an uncommon cardiac tumor that primarily affects infants, children, and young adults. While complete surgical resection generally leads to a favorable prognosis, accurate diagnostic tests remain limited. Case presentation We describe the case of a 26-year-old female who had a dual tumor inside and outside the heart and was misdiagnosed by echocardiography and MRI. We also review 71 cases of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Some rare locations include the esophagus [ 15 ], the pericardium [ 12 ], the heart [ 7 ], the spinal meninges [ 15 ], and the adrenal glands [ 16 , 17 ]. A case describing the simultaneous location of IMT lateral to the ascending aorta near the root and inside the atrial septum has been reported [ 18 ]. IMT may also occur in pregnant women, potentially leading to pregnancy complications and worsening symptoms after delivery [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some rare locations include the esophagus [ 15 ], the pericardium [ 12 ], the heart [ 7 ], the spinal meninges [ 15 ], and the adrenal glands [ 16 , 17 ]. A case describing the simultaneous location of IMT lateral to the ascending aorta near the root and inside the atrial septum has been reported [ 18 ]. IMT may also occur in pregnant women, potentially leading to pregnancy complications and worsening symptoms after delivery [ 19 ].…”
Section: Introductionmentioning
confidence: 99%